Preference of Photographs: A study on significance of photojournalism in newspapers - MAJMC, S Gopika Jayan; Babu, S.Dinesh (International Journal of Psychosocial Rehabilitation, 2020)
India can be marked as a country which gave a place for printed newspaper from the late 16th century. From Hickey’s Bengal Gazette Indians have shaped their taste to attain information from letters and words. Photographs are the integral part of a newspaper because as they give a visual evidence to the audience. But today when print media face crisis it is necessary to check the space given to photograph in newspaper. The research is to assess the importance of photographs in newspaper. A study is conducted among four newspapers the Times of India, the Hindu as English newspaper, Malayala Manorama and Mathrubhumi as Malayalam newspaper. Newspapers from the very first month of 2020, January is taken for the analysis. Kochi edition of the four newspapers for 30 days, the photographs are being calculated based on the five main categories. Regional, National, International, Sports and Environment are the categories considered for the study. The content is analyzed through quantitative methodology to identify which category displays more photograph and a comparison between the four newspapers to find out which paper displays more photographs in the course of 30 days. Also the average photographs displayed by newspapers in their front page and back page are also taken as a part of the study. Therefore, the study will give an idea on how newspaper media values the space to photographs. Also the study will give us an idea on how photographs are distributed among the main sections of the newspaper.